Systems and Their Maintenance - Adds, John.; Larkcom, Erica; Miller, Ruth. (Walton-on-Thames : Nelson, 1998)
This text provides ideal revision opportunities with the inclusion of comprehensive questions at the end of each section, along with answers to encourage self-assessment.
Includes index.
Keywords: Biological systems; Biological systems -- Problems, exercises, etc; Popular Science and Nature